Model bimbingan kelompok dengan art therapy untuk mereduksi stres akademik mahasiswa mengikuti perkuliahan daring dalam kondisi pandemi (Covid-19) - Linda Fitria; Ananda Maha Putri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The process of lecture activities that have just been followed will have an influence on students' condition, such as experiencing academic stress. This study aims to develop a group guidance model using art therapy to reduce academic stress for students attending online lectures during the COVID-19 pandemic. The method used is research and development with an analysis, design, development, implementation and evaluation (ADDIE) approach. The research sample consisted of five students with high academic stress levels and six students with low academic stress levels. Based on the results of data analysis, it is stated that the group guidance model using art therapy can be used to reduce the academic stress level of students who take online lectures.